The Impact of an Educational Intervention Based On PRECEDE - PROCEED Model on Lifestyle Changes among Hypertension Patients - Fatemehsadat Hosseini; Hossein Farshidi; Teamur Aghamolaei; Abdolhossain Madani; Amin Ghanbarnejad (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Hypertension is constantly increasing in different societies. The aim of this study was to determine the impact of educational intervention based on PRECEDE - PROCEED model on the lifestyle changes among hypertension patients in rural health centers of the Jahrom county. Methods: In this experimental study, 40 patients were in the intervention group and 40 patients in the control group. Educational intervention was designed based on PRECEDE - PROCEED model and implemented on the intervention group. The instrument was a researcher-made questionnaire including questions on demographic characteristics and PRECEDE - PROCEED constructs. Data were gathered before and 2 months after the intervention. Data were analyzed using independent sample t-test, paired sample t-test and chi-square test using SPSS19 software. Results: After the intervention, the intervention group than the control group scores of predisposing factors (knowledge and attitudes), reinforcing factors and enabling factors increased significantly among intervention group (p <0.05). The significant increase in levels of physical activity with dietary intervention group improved significantly compared to the control group (p <0.05). Conclusion: The training based on PRECEDE - PROCEED model increases predisposing factors (knowledge and attitudes), enabling and reinforcing factors in patients with hypertension and lifestyle changes especially in increasing physical activity and improving diet is effective.